SystemC and SystemC-AMS in Practice SystemC 2.3, 2.2 and SystemC-AMS 1.0 - Banerjee, Amal; Sur, Balmiki (Springer International Publishing : Imprint: Springer, 2014)
This book describes how engineers can make optimum use of the two industry standard analysis/design tools, SystemC and SystemC-AMS (SystemC 2.3, 2.2 and SystemC-AMS 1.0).  The authors use a system-level design approach, emphasizing how SystemC and SystemC-AMS features can be exploited most effectively to analyze/understand a given electronic system and explore the design space. The approach taken by this book enables system engineers to concentrate on only those SystemC/SystemC-AMS features that apply to their particular problem, leading to more efficient design. The presentation includes numerous, realistic and complete examples, which are graded in levels of difficulty to illustrate how a variety of systems can be analyzed with these tools.    ·          Designed to meet the needs of system designers who need to find an effective/efficient solution in a reasonable period of time; ·          Uses a "hands-on" approach to demonstrate design examples that are complete, realistic and graded in level of difficulty; ·          Demonstrates the most effective use of SystemC/SystemC-AMS tool features, given a particular problem.    .